Effective Inclusive Education Management Guidelines for Children with Special Needs: Case Study of Piboon Prachasan School - Jodkoh, Thanyakorn; Wongkitrungruang, Chairat (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This qualitative research aimed to (1) examine the inclusive education practices implemented at Phibun Prachasarn School, and (2) propose effective approaches for enhancing inclusive education within the school. The key informants consisted of 12 purposively selected participants, including school administrators, homeroom teachers, relevant personnel, parents of children with special needs, and parents of typically developing students who are enrolled in inclusive classrooms. The research instruments used were semi-structured interviews, and the data were analyzed using descriptive content analysis. The study revealed that 1) Phiboon Prachasarn School implemented inclusive education through four key areas: 1.1) Student; The school prepared students with special needs through screening and placement processes, emphasizing readiness in physical, emotional, social, academic, and daily living skills 1.2) Environment; The school provided a physically accessible and supportive learning environment, while promoting positive attitudes and inclusive participation among all staff 1.3) Activity; The curriculum was adapted to meet individual needs, with a focus on hands-on learning, diverse teaching techniques, and career or further education preparation 1.4) Tools; The school allocated annual budgets, received government and scholarship support, and integrated appropriate technologies and learning materials. 2) The proposed effective strategies for inclusive education include 2.1) Student; Expanding structural capacity and adopting flexible classroom arrangements to accommodate increasing numbers of students with special needs 2.2) Environment; Promoting continuous professional development and cultivating a sense of responsibility among educators 2.3) Activity; Building partnerships with workplaces and higher education institutions to create diverse academic and career pathways and 2.4) Tools; Enhancing parental engagement and fostering innovation in student development.